Characterization of the CoFe2O4/Cu displacement effect in the Y123 superconductor matrix on critical properties - Safran, S.; Bulut, F.; Nefrow, A. R. A.; Ada, H.; Ozturk, O. (Springer Science and Business Media LLC, 2020)
In this study, CoFe2O4 (x = 0, 5, 10 and 20 wt%) doped YBa2Cu3−x(CoFe2O4)xO7−δ bulk samples were produced using solid state reaction (SSR) method and sol–gel(SG) methods. Oxide-form and acetate-form powders were preferred for SSR method and SG method, respectively. The heat treatment of the produced samples was carried out in two stages. Firstly, the samples were annealed at 950 °C for 24 h, after which they were kept in oxygen at 500 °C for 5 h and allowed to be cooled down to room temperature. Characterization of all samples was performed using methods such as X-ray diffraction, scanning electron microscopy, energy dispersive spectroscopy, temperature-dependent resistance measurement (R–T) and Vickers microhardness analysis. Superconducting behavior was observed in all the produced samples, but as a result of the addition, a decrease was observed with the increase of the doping ratio at the critical transition temperature. As a result of the characterization, it is concluded that the doping ions can be replaced with Cu atoms in Y123 structure. In addition, doping led to significant changes in Vickers microhardness results.
Keywords: Sol-Gel; Ceramics; Ybco; Transport; Mechanical-Properties; Wires; Transition; Nanoparticles; Y-123; Microstructure